Experimental analysis of an agricultural diesel engine powered with biogas as green fuel from waste canteen food - Kapura Tudu; Debabrata Barik; Sreejesh S. R. Chandran; Prabhu Paramasivam; Jasgurpreet Singh Chohan (Energy Science & Engineering)
Abstract This proposed study aims to characterize and utilize the biogas (BG) derived from the anaerobic co‐digestion of university hostel food waste and Vinasse (waste from the sugarcane industry) in a digester and to run an agricultural diesel engine with BG and Jatropha Curcas methyl ester (JCMS) on a dual fuel (DF) mode. In DF mode, BG from food waste was the main fuel, and JCMS100 was the pilot (secondary) fuel. The engine was run at different BG flow rates as 4, 8, and 12 liters per minute (LPM) with JCMS100 as injected fuel. As per the author's earlier experimental findings, the fuel injection pressure for the JCMS100 was elevated to 240 bar from the base range of 200 bar to enhance the engine performance. The experimental findings for the JCMS, and BG operation were compared with diesel in all aspects. It was revealed that the NOx emission of JCMS100 + 12 LPM of BG was about 7.5% lower than the D100 fuel at full load. Increasing BG intake up to 8 LPM, the BTE increased, however, afterward it started to decline. In a similar consequence, the brake specific fuel consumption (BSFC) declined up to 8 LPM of BG, however, when the engine was fed with 12 LPM of BG the BSFC started to elevate. The carbon monoxide and hydrocarbon also elevated with higher induction of BG. However, interestingly a NOx‐smoke compromised tradeoff was observed for JCME‐BG operation.